Photoinduced Molecular Dynamics in Solution Multiscale Modelling and the Link to Ultrafast Experiments - Levi, Gianluca (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2019)
This book explores novel computational strategies for simulating excess energy dissipation alongside transient structural changes in photoexcited molecules, and accompanying solvent rearrangements. It also demonstrates in detail the synergy between theoretical modelling and ultrafast experiments in unravelling various aspects of the reaction dynamics of solvated photocatalytic metal complexes. Transition metal complexes play an important role as photocatalysts in solar energy conversion, and the rational design of metal-based photocatalytic systems with improved efficiency hinges on the fundamental understanding of the mechanisms behind light-induced chemical reactions in solution. Theory and atomistic modelling hold the key to uncovering these ultrafast processes. Linking atomistic simulations and modern X-ray scattering experiments with femtosecond time resolution, the book highlights previously unexplored dynamical changes in molecules, and discusses the development of theoretical and computational frameworks capable of interpreting the underlying ultrafast phenomena.